ANALISIS PENTAGON FRAUD THEORY DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN - Chan, Michelle; Marlinah, Aan (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
Financial statement fraud is rare in Indonesia. However, when this happens, it can cause a very large loss. The purpose of this research is to examine cases of financial statement fraud in Indonesia through the influence of pentagon fraud as a trigger factor for fraud in financial statements.The population used in this study are manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2021 period. The sampling method used was purposive sampling technique with a sample of 71 companies representing each manufacturing sub-sector. This study uses a logistic regression model.The research method for measuring fraudulent financial reporting uses the F-Score model. This study uses the variable financial statement fraud as the dependent variable. Based on the results of the analysis in this study, it can be concluded that financial targets, financial stability, effective monitoring, nature of industry, changing public accounting firms, changes of directors, and frequent number of CEO's pictures have no effect on fraudulent financial statements. Kecurangan laporan keuangan jarang terjadi di Indonesia. Namun, ketika terjadi dapat menimbulkan dampak kerugian yang sangat besar. Tujuan penelitian ini adalah untuk mengkaji kasus kecurangan laporan keuangan di Indonesia melalui pengaruh pentagon fraud sebagai pemicu faktor kecurangan dalam laporan keuangan. Populasi yang digunakan dalam penelitian ini adalah perusahaan sektor manufaktur yang terdaftar di Bursa Efek Indonesia (BEI) selama periode tahun 2019-2021. Metode pengambilan sampel yang digunakan adalah teknik purposive sampling dengan sampel penelitian sebanyak 71 perusahaan yang mewakili masing-masing subsektor manufaktur. Penelitian ini menggunakan model regresi logistik. Metode penelitian untuk mengukur kecurangan laporan keuangan menggunakan F-Score model. Penelitian ini menggunakan variabel kecurangan laporan keuangan sebagai variabel dependen. Berdasarkan hasil analisis dalam penelitian ini, dapat disimpulkan bahwa financial targets, financial stability, effective monitoring, nature of industry, changing public accounting firms, change of directors, dan frequent number of CEO’s picture tidak berpengaruh terhadap kecurangan laporan keuangan.